Brain Gangliosides in Alzheimer’s Disease: Increased Expression of Cholinergic Neuron-Specific Gangliosides - Fukami, Yuki; Ariga, Toshio; Yamada, Mitsunori; Yuki, Nobuhiro (Current Alzheimer Research, 2017)
Background: Gangliosides are enriched in the neuronal membranes. Gangliosides are shown to interact with amyloid-β proteins, leading to formation of amyloid fibrils in Alzheimer's disease (AD) brains. Several earlier studies indicated that the alterations of ganglioside metabolism could contribute the pathogenesis of AD. Methods: Gangliosides were isolated from the frontal lobes in five patients with AD and three control subjects. Gangliosides were assessed by high performance thin-layer chromatography (HPTLC) with resorcinol staining and immunostaining using mouse monoclonal antibodies against cholinergic neuronspecific (Chol-1α) gangliosides. Results: In all AD brains, not only the total sialic acid content but also a-series gangliosides, GM1 and GD1a, were dramatically reduced as compared with those in control subjects. These results are a hallmark of the pathogenesis in AD. In contrast, Chol-1α gangliosides, GT1aα and GQ1bα, which are specific markers of cholinergic neurons, were significantly increased in AD brains. Conclusion: The expression of Chol-1α gangliosides may be caused by a compensation to preserve the function of the cholinergic neuron and play an important role in cholinergic synaptic transmission.
Keywords: dementia